TRADITIONAL GAME-BASED MANIPULATIVE BASIC MOVEMENT MODEL FOR LOWER GRADE ELEMENTARY SCHOOL CHILDREN - Ali, Masnur; Nugraha, Hartman; Maslikah, Uzizatun; Aqobah, Qory Jumrotul (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2022)
AbstractTraditional games are games that have existed since ancient times and need to be preserved as a characteristic of the nation’s culture. This research aims to create a manipulative basic motion model based on traditional games for lower-grade elementary school children. This research uses the research and development (R&D) method. The research will be conducted by preliminary study with observations, collecting data from the field, and various research results that have been carried out. After obtaining sufficient preliminary data, the next step is to design a suitable and applicable traditional game modification model for basic manipulative skills. Based on the results of suggestions during the small and large trial tests, it was found that 5 traditional games can improve manipulative basic movements, namely: Boy-Boyan, marbles, kasti, engklek, bekel, and gasing. Based on the test results, that game model can be played and improve the manipulative skills of lower-grade elementary school children.Keywords: Manipulative Basic Movement; Traditional Games